2016
DOI: 10.13189/ujas.2016.040202
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Quality Assessment of Hand-dug Shallow Water Wells in Awka Metropolis, Anambra State, Nigeria

Abstract: Bacteriological quality assessment of some hand-dug shallow water wells in Awka metropolis was carried out during the dry and wet seasons to determine their potability. The total bacterial, total coliform, faecal coliform and Vibrio chloreae counts were determined using standard laboratory methods. The total bacterial counts during the dry season ranged from 100 to 300 cfu/100ml; total coliform counts, 42-126 cfu/100ml; faecal coliform counts, 10-26 cfu/100ml and Vibrio cholerae counts, 2-10cfu/100ml. During t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
2

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
1
0
2
Order By: Relevance
“…In this study, four different bacteria were isolated and identified which are Staphylococcus aureus, Salmonella spp, Shigella spp and Escherichia coli and similar findings of some of these bacteria have been earlier reported by several workers [21][22][23][24][25][26][27][28][29][30][31]. Bacteria such as Staphylococcus aureus, Escherichia coli, Salmonella spp, and Shigella spp observed in this study are of public health importance as they have been found to be related to various diseases of man such as gastroenteritis.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this study, four different bacteria were isolated and identified which are Staphylococcus aureus, Salmonella spp, Shigella spp and Escherichia coli and similar findings of some of these bacteria have been earlier reported by several workers [21][22][23][24][25][26][27][28][29][30][31]. Bacteria such as Staphylococcus aureus, Escherichia coli, Salmonella spp, and Shigella spp observed in this study are of public health importance as they have been found to be related to various diseases of man such as gastroenteritis.…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, it was observed in this study that Escherichia coli was the least isolated bacteria, and this is in agreement with the findings of Nwakanma et al [38]; Lawrence et al [27] and Falegan et al [31] respectively. However, these findings were in disagreement with the findings of Edema et al [23]; Ogbonna et al [24]; Samuel et al [26] as well as that of Ananias et al [30] respectively, who reported Salmonella spp, Shigella spp, Streptococcus pyogenes, Pseudomonas spp and Staphylococcus aureus and Lactobacter species respectively as the least bacteria isolates recorded. The findings from this study shows that the level of hygienic practices of the Tsire meat processing by the sellers affect the level of contamination of the meat, even though the results are within the range of satisfactory and marginal when compared with the guidelines of microbiological examination of ready-to-eat food samples.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation